Estimation of Reaction Rates of Transesterification Pathways - Pérez-Méndez, Mario Alberto; Jiménez-García, Gladys; Huirache-Acuña, Rafael; Maya-Yescas, Rafael (Frontiers in Chemical Engineering, 2021)
Experimental estimation of reaction rates is a common aspect of reaction engineering because reaction kinetics are the base of the design of chemical reactors. However, it is not easy to follow complex reactions as it is the case of transesterification of triglycerides in presence of sodium hydroxide. Identifying the possible reaction pathways taking place as ionic and sequential, starting with the inorganic formation of methoxide, and followed by each one of the three organic transesterification steps of virgin soybean oil, deeper understanding about kinetics of this reacting path has been obtained. Reaction rate evaluations were performed by following the solution’s pH, based on a 2^(4-1) design of experiments, making possible to estimate the rate constants. Additionally, it was observed that there is an optimum amount of sodium hydroxide feed to the process, therefore it is possible to minimize its addition, which favors diminishing the volume of leaching water. The best yield of the reaction for fatty acid methyl esters production, with minimum addition of sodium hydroxide, was 98.84 wt.%, which is highly competitive.